Pengaruh model pembelajaran Group Investigation (GI) pada mata pelajaran geografi terhadap kemampuan memecahkan masalah siswa kelas XI IPS SMA Negeri 1 Singosari - Lia Yulistiana; Yuswanti Ariani Wirahayu; Didik Taryana (Universitas Negeri Malang, 2023)
The ability to solve problems is the availability of a person in the process of thinking and solving a problem, the ability to solve problems needs to be possessed by students, especially high school students. This study aims to determine the effect of the group investigation on the subject of Geography on the problem-solving ability of students in SMA Negeri 1 Singosari, Malang Regency, class XI Social Sciences. The research subjects were XI IPS A as the experimental class and XI IPS B as the control class. The instrument in this study used descriptive questions to measure students' ability to solve learning problems. Data analysis used independent sample t-test using SPSS 2.0 for Windows. The ability to solve learning problems in experimental class students with an average gainscore (18,48) is significantly different from the control class (16,6). This shows that the difference in problem solving abilities of the experimental class students is higher than the control class because the experimental class is given special treatment by using the group investigation learning model. Based on this, it can be concluded that there is an effect of using the group investigation in the Geography learning process on the problem solving ability of students in SMA Negeri 1 Singosari, Malang Regency, class XI Social Sciences. Kemampuan memecahkan masalah adalah ketersediaan seseorang dalam proses pemikiran dan penyelesaian dari suatu masalah, kemampuan memecahkan masalah perlu dimiliki oleh siswa terutama siswa SMA. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran group investigation pada mata pelajaran Geografi terhadap kemampuan memecahkan masalah siswa SMA Negeri 1 Singosari Kabupaten Malang kelas XI IPS. Subjek penelitian XI IPS A sebagai kelas eksperimen dan XI IPS B kelas kontrol. Instrumen penelitian adalah soal uraian sebagai alat ukur kemampuan siswa memecahkan masalah Geografi. Analisis data dilaksanakan dengan uji independent sample t-test dengan menggunakan SPSS 2.0 for Windows. Kemampuan memecahkan masalah Geografi di kelas eksperimen dengan hasil rata- rata gainscore (18,48) hal tersebut berbeda signifikan dengan kelas kontrol (16,6). Hal ini menunjukan bahwa perbedaan kemampuan memecahkan masalah siswa kelas eksperimen lebih tinggi daripada kelas kontrol dikarenakan kelas eksperimen diberikan perlakuan khusus dengan penggunaan model pembelajaran group investigation. Dapat disimpulkan terdapat pengaruh penggunaan model pembelajaran group investigation pada proses pembelajaran Geografi terhadap kemampuan memecahkan masalah siswa SMA Negeri 1 Singosari Kabupaten Malang kelas XI IPS.